Burden of adverse childhood experiences in children attending paediatric clinics in South Western Sydney, Australia: a retrospective audit - Pankaj Garg; Yuanee Mary Wickramasinghe; Shanti Raman; Romy Hurwitz (BMJ Publishing Group, 2019)
Objectives Adverse childhood experiences (ACE) are associated with poor short, medium and long-term health outcomes. South Western Sydney (SWS) has a large culturally diverse population, including many disadvantaged population groups. Our aims were to determine the burden of ACE in children attending community paediatric (CP) clinics using a purposefully developed ACE checklist, and explore any association with developmental health of children.Methods We trialled the ACE checklist in all CP clinics including child development (CD) and vulnerable child (VC) clinics between February 2017 and August 2017. Data were collated from completed ACE checklists and relevant clinical information from CP clinics. Statistical analysis was performed using SPSS and MedCalc software.Results Of 279 children seen in CP clinics with checklists completed for the period, 167 (60%) attended CD clinics and 112 (40%) attended VC clinics. Seventy-eight (28%) had ACE ≥4 and 178 (64%) had ACE ≥1. Of those attending CD clinics, 8 (5%) had ACE ≥4 compared with 70 (63%) attending VC clinics (p<0.001). Of all age groups, children ≥10 years of age had the highest proportion of children with ACE ≥4 (65%); significant association between age group and ACE ≥4 (p<0.001). There was a significant association between cultural background and ACE ≥4 (p<0.001); indigenous children had the highest proportion of ACE ≥4 (n=21; 64%), followed by Anglo-Australian children (55%). On logistic regression analysis, only attending VC clinics was significantly associated with ACE ≥4. There was no significant association between ACE ≥4 and developmental health.Conclusion Among children attending CP clinics in SWS, more than a quarter had a significant burden of ACE; those attending specialised clinics for vulnerable children, those from particular ethnic groups and from older age groups, had the highest burden of ACE. Our findings support the need for specialised pathways for paediatric assessment for vulnerable, at-risk children.